The role of expansion angle and speed on shish-kebab formation in expansion pipe extruder head explored by high temperature rapid stretch. (December 2021) - Pan, Yuxi; Li, Nan; Wang, Jinyan; Wang, Danhui; Pan, Xiaotong; Liu, Cheng; Jian, Xigao
Abstract: Morphology and microstructures play a significant role on properties of polymer products. Self-reinforced shish-kebab formed inside the products by elongational flow induced orientation can improve the tensile strength and pressure rating properties, and the density of polymers consisting of shish-kebabs is fairly below those filled with glass fibers, basalt and talc. The threshold parameters to form shish-kebab structure in a novel annular expansion pipe extruder head were determined by high temperature rapid stretch (HTRS) in this study. Different morphologies of HDPE specimens made under the conditions in expansion head by HTRS were studied by SEM, 2D-WAXD and 2D-SAXS, specimen 7 with 15° and 6 mm/s base speed has the optimal shish-kebab structure and specimen 10 with 30° and 5 mm/s has the best orientation parameter and the best shish structure. The DSC results agree well with the morphology results shown in the SEM images. The specimen 7 displays the highest tensile strength, increases about 187% compared with the reference specimen. These outstanding properties were attribute to the perfect and compact shish-kebab structures inside it. The results of HTRS can prove a direction guide for extrusion processing. Highlights: HTRS was used to simulate the melt flow state and crystal state in extruder head before the start of the extrusion. The results of HTRS can be used for preliminary verification of the finite element simulation results inside the extruder. The threshold condition of shish-kebab formation was found using the HTRS and the results can apply to the extrusion process. The results of HTRS could provide a good guide for the subsequent polymer extrusion processing.